High switching efficiency in FePt exchange coupled composite media mediated by MgO exchange control layers - Dutta, Tanmay (2017)
Satisfying the mutually conflicting requirements of easy switchability and high thermal stability still remains a hindrance to achieving ultra-high areal densities in hard disk drives. Exchange coupled composite media used with proper exchange control layers (ECLs) presents a potential solution to circumvent this hindrance. In this work, we have studied the role of MgO and Ta ECLs of different thicknesses in reducing the switching field of FePt media. MgO ECL was found to be more effective than a Ta ECL. For a 2 nm MgO ECL, the switching field could be reduced by 41% and at the cost of only a limited loss in thermal stability. Furthermore, a very high switching efficiency of 1.9 was obtained using 2 nm MgO ECL. So, with a proper choice of ECL material and thickness, the switching field of FePt media can be substantially reduced while ensuring high thermal stability and a better signal-to-noise ratio, thus potentially paving the way for very high areal density media.